2018
DOI: 10.1021/acs.macromol.8b00489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Assembly of Oxalamide Based Organic Compounds on Melt Behavior, Nucleation, and Crystallization of Isotactic Polypropylene

Abstract: We report on the effect of an aliphatic oxalamide based nucleating agent (OXA3,6) on the melt and crystallization behavior of isotactic polypropylene (iPP) under defined shear conditions. Through polarized optical microscopy, we demonstrate that OXA3,6 self-assembles from the iPP melt into rhombic crystals whereas their size and distribution proved highly dependent on the employed cooling rates. The presence of 0.5 wt % of OXA3,6 in iPP results in a significant suppression in iPP melt viscosity, which could no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 50 publications
5
21
0
Order By: Relevance
“…Additionally, it may be concluded that at 220 °C the complex viscosity decreases slightly with increasing OXA3,6 concentration throughout the evaluated frequency range. In line with previous observations, 24 these findings confirm that OXA3,6 facilitates a viscosity suppression in i PP.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Additionally, it may be concluded that at 220 °C the complex viscosity decreases slightly with increasing OXA3,6 concentration throughout the evaluated frequency range. In line with previous observations, 24 these findings confirm that OXA3,6 facilitates a viscosity suppression in i PP.…”
Section: Resultssupporting
confidence: 93%
“…With respect to the viscosity suppression, earlier, with the help of molecular modeling, we concluded that the OXA3,6 concentration is far too low to facilitate the observed enhancement in molecular relaxation, thus excluding the possibility that OXA3,6 acts as a solvent for i PP. 24 This implies that there should be some sort of interaction between the OXA3,6 molecules and the i PP chains, where the average effect is the speed-up of the chain dynamics, especially the large scale reorientation of the chains (i.e., in the terminal regime). According to the data provided in Figure 3, this interaction should not cause any significant disruption of the entanglement network.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations